A Critical Study of Arabic Language Learning for Early Childhood in Modern Literature: A Qualitative Analysis of Approaches and Digital Media - Mutia Risnadila Bintoro; Ahmad Nur Mizan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to critically examine modern literature on Arabic language learning for early childhood (AUD) with a focus on pedagogical approaches and the use of digital media. Using a qualitative research method in the form of a library research with a critical discourse analysis approach, this study examines 30 journal articles indexed in SINTA and Scopus published between 2019 and 2024. The results show a paradigm shift from memorization-based methods to communicative and multisensory approaches integrated with interactive digital applications. However, key challenges include teacher readiness, lack of content appropriate for children's cognitive development, and digital overstimulation. These findings imply the need for a curriculum framework that accommodates a balance between digital exposure and socio-affective interaction.